GENOME ASSEMBLY OF INDONESIAN TURMERIC (CURCUMA LONGA L.) THROUGH WHOLE GENOME SEQUENCING - Jason Wiguna, Fransiscus
Turmeric (Curcuma longa L.) is a medicinal plant with high global competitiveness. Therefore, the development of superior Indonesian turmeric varieties is necessary to compete in the international market. Molecular breeding through marker asisted selection is required to develop superior traits. Accurate marker positions are obtained from high-resolution draft genome. This study aims to establish the draft genome of Indonesian turmeric. Turmeric leaf samples were collected from the Ciparanje experimental field at Universitas Padjajaran. Genomic DNA isolation from the G26.1 accession resulted a concentration of 50.4 ng/?l with an A260/A280 absorbance ratio of 1.83, which confirmed as Curcuma longa through DNA barcoding with ITS2 gene. The G26.1 accession was sequenced using Illumina NovaSeq 6000, resulted 150 million Paired-End Reads with a length of 150 bp and a total size of 22.5 Gbp. Genome size and ploidy level predictions were made using GenomeScope and Smudgeplot, resulted a genome size of 641-661 Mpb and a diploid character. The draft genome assembly resulted in a size of 659 Mbp, an N50 score of 8 Mbp, and a BUSCO completeness percentage of 78.4%. This research provides basic information for future studies in genome assembly at the chromosome level, which can be utilized as a reference for the construction of a SNP database.